2018
DOI: 10.1088/1748-0221/13/12/p12028
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wavelength-shifting fibers for the Mu2e cosmic ray veto detector

Abstract: The cosmic-ray-veto detector (CRV) for the Mu2e experiment consists of four layers of plastic scintillating counters read out by silicon photo-multipliers (SiPM) through wavelength-shifting fibers. This paper reports the light properties of several wavelength-shifting fiber samples with diameters of 1.0 mm, 1.4 mm, and 1.8 mm that were considered for the CRV system. A fiber diameter of 1.4 mm was selected as optimal for the CRV, and measurements of the prototype and production fiber of this diameter are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Instead, the estimated efficiency (based on measured quantities, see table 1) is pre-applied to the number of initial EUV photons. The probability of a photon to reach a SiPM once it has been successfully wavelengthshifted in a fiber is determined by the product of the Y-11 fiber trapping efficiency assuming a doubleclad fiber with readout from both sides [15], transmission efficiencies in the Y-11 fibers (length of 4 * 1.5 m = 6 m) [26,27] and clear fibers (length of 7 m) [28], and losses from fiber transitions [29] and bends. Taking the product of the efficiencies in table 1, 3.32% of green photons produced in the WLS fibers will be transmitted to the SiPM readout.…”
Section: Jinst 17 T04007mentioning
confidence: 99%
“…Instead, the estimated efficiency (based on measured quantities, see table 1) is pre-applied to the number of initial EUV photons. The probability of a photon to reach a SiPM once it has been successfully wavelengthshifted in a fiber is determined by the product of the Y-11 fiber trapping efficiency assuming a doubleclad fiber with readout from both sides [15], transmission efficiencies in the Y-11 fibers (length of 4 * 1.5 m = 6 m) [26,27] and clear fibers (length of 7 m) [28], and losses from fiber transitions [29] and bends. Taking the product of the efficiencies in table 1, 3.32% of green photons produced in the WLS fibers will be transmitted to the SiPM readout.…”
Section: Jinst 17 T04007mentioning
confidence: 99%
“…The Mu2e collaboration which also uses Kuraray Y-11 WLS fibres has measured the attenuation length of the fibres, but over substantially longer fibre lengths of 25 m. In a 2015 study they applied a double-exponential fit to their data of the same form shown in equation (6.1) and extracted short and long attenuation lengths of 4.76 and 9.02 m, respectively [34]. A later study in 2018 separated the data into two independent exponential fits over the ranges 0.5-3.0 m and 3.0-25.0 m, and again extracting short and long attenuation lengths, this time of 5.1 ± 0.2 and 8.2 ± 0.1 m, respectively [35]. In both cases their short attenuation length measurement is consistent with the (double-ended readout bars) long attenuation lengths we have obtained.…”
Section: Jinst 17 P10028mentioning
confidence: 99%
“…Fiber choice. Kuraray Y-11 fibers [20] have been thoroughly characterized by multiple experimental groups [21][22][23]. The Y-11 absorption spectrum has good overlap with the TPB emission spectrum [13,14], and the Y-11 emission spectrum is peaked near 500 nm, well-suited for many SiPMs.…”
Section: Design and Implementation Detailsmentioning
confidence: 99%